Odpowiedź:
a) y = x2 + 4x + 3
y = (x+2)^2 - 1/2
b) y = ½ x2 + x – ½
y = 1/2(x+1)^2 - pierwiastek z 2 / 2
Szczegółowe wyjaśnienie:
a) y = x2 + 4x + 3
a = 1
b = 4
c = 3
Delta = b^2-4ac = 4^2 - 4*1*3 = 16-12 = 4
Pierwiastek z 4 = 2
Delta = 2
Postać kanoniczna:
y = a(x-p)^2+q
p = -b/2a q = -delta/4a
p = -4/2 = -2
q = -2/4 = -1/2
y = 1*(x+2)^2+(-1/2)
y = (x+2)^2 - 1/2
b) y = ½ x2 + x – ½
a = 1/2
b = 1
c = - 1/2
Delta = b^2-4ac = 1^2-4*1/2*(-1/2) = 1+1 = 2
Delta = Pierwiastek z 2
Postać kanoniczna:
y = a(x-p)^2+q
p = -b/2a q = -delta/4a
p = -1/(2*1/2) = -1/1 = -1
q = - pierwiastek z 2/(4*1/2) = - pierwiastek z 2/2
y = 1/2(x+1)^2 - pierwiastek z 2 / 2